OBSESI KONSUMEN DAN ETIKA PEMASARAN (ERA BARU PEMASARAN) - Susanti, Retno - (Universitas Slamet Riyadi, 2011)
ABSTRACT Globalization and technological change as well as the more mature consumer behavior to determine what needs to be done to meet the needs and to whom they hung fulfilling the needs and desires (how to satisfy Their own need and want), can be difficult and is the starting point for a company that maintains the approach of death old-paradigm approach and company oriented. In order to survive they must change the direction of the business customer care and marketing ethics. Namely to 1) the ability of adaptability, efficiency and flexibility in conducting pro actions and reaction 2) guarantee the quality of products intended to retain potential customers not to switch to competitors that do not pay for